PENINGKATAN KETERAMPILAN MENYIMAK CERITA ANAK MELALUI MEDIA ANIMASI AUDIO VISUAL PADA SISWA KELAS IV SDN SUNGGUMINASA II - Ismail; Rexy Fernanda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The main problem in this research is whether the use of audio-visual animation media can improve listening skills in class IV students at SDN Sungguminasa II. This research aims to describe improving the quality of children's story listening skills through audio-visual animation media in class IV students at SDN Sungguminasa II. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out in two meetings. Research procedures include planning, implementing actions, observing and reflecting. The subjects of this research were 32 grade IV students at SDN Sungguminasa II. The research results showed that the first cycle test results had a class average score of 71.4 and were in the sufficient category. This score has met the target set, namely 70. In this cycle, students experienced an increase of 13.3 points from the pre-action score. Meanwhile, in cycle II, the average score reached 83.9, which means there was an increase from cycle I of 12.5 points. The average value is in the good category. The increase in children's story listening skills from pre-action to cycle II was 25.8 points. Based on the results of the research above, it can be concluded that listening skills through audio-visual animation media in class IV students at SDN Sungguminasa II have increased.